The Influence of Social Media Use and Financial Experience on Financial Management Behavior with Self-Control as a Moderating Variable on Career Women in Surabaya City - Ervanto, Khansa Florensa; Anwar, Muhadjir (PT FORMOSA CENDEKIA GLOBAL, 2024)
Financial management behavior refers to the ability to manage finances effectively, which includes planning, budgeting, controlling spending, conducting financial audits, and seeking and saving funds for daily financial needs. This study aims to examine the influence of social media usage and financial experience on financial management behavior, with self-control as a moderating variable. The population consisted of career women working in the formal sector in Surabaya City. The study included 170 respondents selected through purposive sampling, and data were collected using questionnaires with analysis conducted using Partial Least Squares (PLS). The results indicate that social media usage has a positive influence on financial management behavior, and financial experience also has a positive influence on financial management behavior. Self-control does not moderate the relationship between social media usage and financial management behavior, but self-control does moderate the relationship between financial experience and financial management behavior.